KERAWANAN BAHAYA LONGSOR PADA KAWASAN TERBANGUN KOTA BOGOR - Dewi, Indarti Kolama; Akbar, Aldira (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2025)
Landslides are the most common type of disaster in Bogor City compared to other disasters. The large number of built-up areas that are not following the Bogor City Spatial Plan (RTRW) has the potential to cause disasters that can result in material losses and fatalities. The objectives of the study: 1) Identifying the level of landslide susceptibility in Bogor City, 2) Identifying the level of landslide susceptibility in built-up areas in Bogor City. This study used the Geographic Information System (GIS) method using 5 landslide susceptibility parameters, namely: rainfall, rock type, soil type, slope, and land use. The results of this study indicate that from the area of Bogor City of 11,130.31 ha, areas with low level of  landslide susceptibility are 50,20%, areas with moderate level of landslide susceptibility are 46,36%) and areas with high level of landslide susceptibility are 383.54 ha (3,45%). The built-up area in Bogor City is 6,274.34 ha, low landslide susceptibility is 60,69%, medium landslide susceptibility is 54,35% and high level of  landslide susceptibility is 20,65%. There are built-up areas that are in line with the Bogor City Spatial Plan 2011-2031 with a moderate landslide susceptibility level of 45.44% and a high landslide susceptibility level of 16.87%. Based on these findings, the Bogor City Government can proactively reduce disaster risks in areas with medium and high landslide susceptibility. To mitigate it, stricter spatial planning controls and Building and Environmental Planning  are needed for settlements located in areas with high landslide susceptibility.